GAYA BELAJAR SISWA KELAS III A DALAM PEMBELAJARAN TEMATIK DI MIN 3 BANTUL YOGYAKARTA - Wuriyani Wuriyani; Samsudin Samsudin; Muhammad Asrofi; Ahmad Shofiyuddin Ichsan (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
Abstract. The purpose of this study is to determine student learning styles, teacher strategies in teaching based on student learning styles, and the implications of student learning styles in Thematic learning in class III A MIN 3 Bantul Yogyakarta. The research is conducted using qualitative methods, with the type of field research, data collection techniques are carried out by observation, documentation and interviews. While the data analysis used Sugiyono's Circular model, namely the descriptive stage, the reduction stage and the selection stage. The results of the data analysis are: 1) There are six types of learning styles in class III MIN 3 Bantul, namely verbal, aural, kinesthetic, visual, logical, and social learning styles. Of the six student learning styles, the dominant frequency of student learning styles in this class is the kinesthetic learning style. 2) There are several specific strategies from the teacher in teaching based on students’ learning styles of class III A by adjusting their classes. 3). There are two implications of student learning styles in class III A MIN Bantul Yogyakarta in Thematic learning, namely using mental science in the application of student learning styles and the importance of knowing student learning styles.